(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Antibiotics have improved the health of countless numbers of humans and animals, antibiotics have been losing their effectiveness since the beginning of the antibiotic era. The use of antibiotics in raising food animals has contributed significantly to the global pool of antibiotic resistant organisms. There is no doubt that the use of antibiotics provides selective pressure that results in resistant bacteria and resistance genes. While some resistant bacteria are found naturally in the environment, pathogens and non-pathogens are released into the environment in several ways, contributing to a web of resistance that includes humans, animals, and the environment. Reviewed here are the history and scope of both antibiotics and resistance, the mechanisms of resistance, and evidence for the spread of antibiotic resistant organisms and resistance genes through humans, animals, and the environment. In this paper we study about the reviews of different writer which was also a study about Antibiotics.